Rotigotine's effect on PLM-associated blood pressure elevations in restless legs syndrome: An RCT. (10th May 2016) - Bauer, Axel; Cassel, Werner; Benes, Heike; Kesper, Karl; Rye, David; Sica, Domenic; Winkelman, John W.; Bauer, Lars; Grieger, Frank; Joeres, Lars; Moran, Kimberly; Schollmayer, Erwin; et al.
Abstract : Objective: This double-blind, placebo-controlled, interventional trial was conducted to investigate the effects of rotigotine patch on periodic limb movement (PLM)–associated nocturnal systolic blood pressure (SBP) elevations. Methods: Patients with moderate to severe restless legs syndrome (RLS) were randomized to rotigotine (optimal dose [1–3 mg/24 h]) or placebo. Continuous beat-to-beat blood pressure (BP) assessments were performed during polysomnography at baseline and at the end of 4-week maintenance. Primary outcome was change in number of PLM-associated SBP elevations (defined as slope of linear regression ≥2.5 mm Hg/beat-to-beat interval over 5 consecutive heartbeats [≥10 mm Hg]). Additional outcomes were total SBP elevations, PLM-associated and total diastolic BP (DBP) elevations, periodic limb movements index (PLMI), and PLM in sleep arousal index (PLMSAI). Results: Of 81 randomized patients, 66 (37 rotigotine, 29 placebo) were included in efficacy assessments. PLM-associated SBP elevations were significantly reduced with rotigotine vs placebo (least squares mean treatment difference [95% confidence interval (CI)] −160.34 [−213.23 to −107.45]; p < 0.0001). Rotigotine-treated patients also had greater reduction vs placebo in total SBP elevations (−161.13 [−264.47 to −57.79]; p = 0.0028), PLM-associated elevations (−88.45 [−126.12 to −50.78]; p < 0.0001), and total DBP elevations (−93.81 [−168.45 to −19.16]; p = 0.0146), PLMI (−32.77 [−44.73 to −20.80]; p < 0.0001), and PLMSAI (−7.10 [−11.93 to −2.26]; p = 0.0047). Adverse events included nausea (rotigotine 23%; placebo 8%), headache (18% each), nasopharyngitis (18%; 8%), and fatigue (13%; 15%). Conclusions: Further investigation is required to determine whether reductions in nocturnal BP elevations observed with rotigotine might modify cardiovascular risk. Classification of evidence: This study provides Class I evidence that for patients with moderate to severe RLS, rotigotine at optimal dose (1–3 mg/24 h) reduced PLM-associated nocturnal SBP elevations.